2019
DOI: 10.3390/ijerph16162954
|View full text |Cite
|
Sign up to set email alerts
|

Recent Incidence of Human Malaria Caused by Plasmodium knowlesi in the Villages in Kudat Peninsula, Sabah, Malaysia: Mapping of The Infection Risk Using Remote Sensing Data

Abstract: Plasmodium knowlesi (Pk) is a malaria parasite that naturally infects macaque monkeys in Southeast Asia. Pk malaria, the zoonosis transmitted from the infected monkeys to the humans by Anopheles mosquito vectors, is now a serious health problem in Malaysian Borneo. To create a strategic plan to control Pk malaria, it is important to estimate the occurrence of the disease correctly. The rise of Pk malaria has been explained as being due to ecological changes, especially deforestation. In this research, we analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Assessment of human and environmental factors associated with knowlesi -malaria risk found that interactions and sighting of macaque species, predominantly Mf , was associated with an increased risk of acquiring P. knowlesi infection [ 66 ]. The findings also support a consistent risk factor profile for knowlesi -malaria with men working as subsistence farmers, especially those who work in palm-oil plantations, with the highest individual transmission risk occurring at the forest fringe [ 19 , 61 , 66 , 77 ]. Investigations into peri-domestic transmission and exposure to P. knowelsi in Sabah, Malaysia, found that the primary vector, An.…”
Section: Ecological Drivers Of Plasmodium Knowlesi supporting
confidence: 57%
See 1 more Smart Citation
“…Assessment of human and environmental factors associated with knowlesi -malaria risk found that interactions and sighting of macaque species, predominantly Mf , was associated with an increased risk of acquiring P. knowlesi infection [ 66 ]. The findings also support a consistent risk factor profile for knowlesi -malaria with men working as subsistence farmers, especially those who work in palm-oil plantations, with the highest individual transmission risk occurring at the forest fringe [ 19 , 61 , 66 , 77 ]. Investigations into peri-domestic transmission and exposure to P. knowelsi in Sabah, Malaysia, found that the primary vector, An.…”
Section: Ecological Drivers Of Plasmodium Knowlesi supporting
confidence: 57%
“…At a local scale in Malaysian Borneo, ~80% of the forest landscape has undergone deforestation or agriculture expansion between 1990 and 2009, leaving only 3–8% of protected forests intact [ 60 ]. Deforestation in this region is typically attributable to the rapid development of industrial plantations [ 61 ], with this trend likely to continue [ 62 ]. When considering these factors, it highlights the potential consequences of decimating ecosystems and the increased threat of zoonotic disease outbreaks [ 58 ].…”
Section: Ecological Drivers Of Plasmodium Knowlesi mentioning
confidence: 99%
“…monkeys (Moyes et al 2016). This is a particular problem in Malaysian Borneo, where a risk map was developed to visualise land use and assess malaria risk distributions (Sato et al 2019). Such mapping approaches can help determine the risk factor for vector‐spread protozoa under LUC, enabling people to predict and mitigate outbreaks.…”
Section: Resultsmentioning
confidence: 99%
“…Viruses of notable concern include henipaviruses in Africa (Pernet et al 2014), Hendra virus in Australia (Wild 2009), and Nipah virus in Malaysia (Field 2009). Likewise, non‐human primates show an increase in zoonotic parasites with fragmentation of forests (Gillespie 2006); parasites include plasmodium (Moyes et al 2016, Sato et al 2019) and a range of helminth species (Klaus et al 2017). In Sri Lanka, habitat fragmentation from deforestation has led to wild animals roaming in nearby neighbourhoods, increasing the exposure of residents to ticks and the risk of tick‐borne infections (Liyanaarachchi et al 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation